THE INFLUENCE OF LEARNING STYLES AND LEARNING METHODS ON LEARNING OUTCOMES - Haris, Abdul; Purnamasari, Pupung (LP2M IBK Nitro, 2025)
In this study, the main objective is to analyze the impact of learning styles and teaching methods on students’ learning outcomes. There are various learning styles, such as visual, auditory, and kinesthetic, which can influence how students absorb and understand information. This research is based on several previous studies that indicate aligning teaching methods with students’ learning styles can significantly enhance academic performance. For instance, a study conducted by Rusmana and Wulandari (2020) showed that students whose learning styles matched the teaching methods used achieved better results in mathematics. Furthermore, Adawiyah et al. (2020) found that students’ learning outcomes in science subjects were also affected by the applied learning styles. Therefore, understanding the relationship between learning styles and teaching methods is crucial to improving the effectiveness of the teaching and learning process in the classroom.